Magnetic Nano-Sized SDF-1 Particles Show Promise for Application in Stem Cell-Based Repair of Damaged Tissues - Wang, Xu; Han, XinXin; Qiu, Yi; Sun, Jianbo (Frontiers in Bioengineering and Biotechnology, 2022)
Stem cell-based therapy is a promising option for the repair of injured tissue. Stem cells have homing characteristics and can be mobilized to the injury sites following activation, under the regulation of the SDF-1/CXCR4 axis. However, a sufficient level of stem cell aggregation and retention is essential for ensuring favorable repair outcomes. Problems related to stem cell delivery/recruitment efficiency and retention in the injury site are among the main challenges faced during in vivo studies on stem cell therapy. In this study, we designed an SDF-1(alpha) magnetic nanoparticle delivery system for stem cell recruitment. We expressed and purified a biotin-labeled SDF-1(alpha) protein and immobilized it on streptavidin-modified magnetic nanoparticles (MNPs) through the streptavidin-biotin linkage, with an efficiency of approximately 14%. The physicochemical properties of the SDF-MNPs in glycerol buffer were similar to those of the streptavidin-modified MNPs. Further evidence suggested that SDF-MNPs show barely cytotoxicity even at a concentration of 125 µg/mL MNPs and have a promising chemotaxis effect on MSCs in vitro and in vivo. Our study provides a strategy for the assembly of magnetic nanoparticle carrier systems for protein factors, as well as preliminary evidence for the application of SDF-MNPs in stem cell-based therapy for the regeneration of injured bone tissue.